A proposed organic Schottky barrier photodetector for application in the visible region - Dwivedi A.D.D.; Singh A.K.; Prakash R.; Chakrabarti P. (My University, 2025)
The fabrication and characterization of an organic photodetector (OPD) in the form of ITO coated glass/polycarbazole (PCz)/Al Schottky contact is reported. The device has been fabricated in our laboratory for the first time using the polymer synthesized by us. The device has been subsequently characterized in respect of electrical and optical properties in order to explore its potential for possible use as a detector in the visible region at 650 nm. It is observed that the detector exhibits a reasonably high value of peak detectivity (∼6 × 106 cm Hz1/2 W-1) near zero bias voltage at V = 0.2 V. © 2009 Elsevier B.V. All rights reserved.